Direct torque control of IM using PID controller - Ali Najim Abdullah; Mohammed Hasan Ali (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Direct torque control "DTC" technique is one of a high performance control system of an AC motor drive, which was proposed after the vector oriented control scheme during the resent 25 years. It has been developed rapidly for its concise system scheme, transient and dynamic performance. The DTC mechanism consists of voltage vector selection table, two hysteresis comparators and two estimators one for stator flux and another for electromagnetic torque. DTC is directly control torque and flux by using Voltage Source Inverter VSI, space vector and stator flux orientation and indirect speed regulated. A several control techniques can be used for improving the torque and flux performance. In this paper, the DTC with Proportional-Integral-Derivative (PID) controller used to improve the starting and dynamic performance of asynchronous motor AM, which gives good torque and flux response, best speed control and also minimize the unacceptable torque ripple. The mathematical model of DTC with PID controller of 3-phase induction motor IM are simulated under Matlab-Simulink. Therefore, the DTC based on PID controller has good performance of IM compared to classical DTC for starting, running state and also during change in load.